Estimated annual increments in stature and weight among soccer players 11–18 years - Malina, Robert; Martinho, Diogo; Oliveira, Tomas; Celis-Moreno, Jorge M.; J. Figueiredo, António; Seabra, Andre; Konarski, Jan; Cumming, Sean; Coelho-e-Silva, Manuel (Biology of Sport, 2025)
Annual increments in height and weight were estimated in a mixed-longitudinal sample of Portuguese male soccer players 11–14 years at baseline. This study aims to compare estimated increments with reference values for the general population and also with estimates from youth soccer literature. The sample included 87 under-13 (U13) and 72 under 15 (U15) players. Allowing for drop-outs and/or transfers, participants were followed over five seasons. Annual measurements of height and weight were taken for the total mixedlongitudinal sample of 571 players, from which annual increments were calculated for 409 occasions. Mean heights and weights of the sample and median annual increments were compared with corresponding estimates for the general population in addition to soccer players based on studies spanning 2000–2015. Mean heights of the sample were slightly but consistently less than the reference, while mean weights were below the reference at 11–13 years and approximated the reference at 14–18 years. Median annual height and weight increments of the soccer players approximated the respective medians for the general population, but increments among individual players varied considerably with age. In contrast, the heights and weights of the Portuguese players were below the means for the composite sample of soccer players except at 18 years, but estimated increments were similar to the composite sample. In summary, increments in the heights and weights of the Portuguese players approximated the general population and means for other soccer players, while mean heights were consistently less than the reference except at 18 years.